Composite hollow fiber membrane and preparation method thereof

By forming the interaction between silicon oxide and polymer chain in situ in the composite hollow fiber membrane, the problem of membrane performance degradation caused by the agglomeration of inorganic nanoparticles is solved, the stable dispersion of inorganic particles and the improvement of membrane performance is achieved, and the water filtration is improved and fluid separation effect.

CN119236698APending Publication Date: 2025-01-03NINGBO JIANRONG SPECIAL SEPARATION MEMBRANE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411682592.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The agglomeration of inorganic nanoparticles in the existing composite water treatment membranes causes the membrane to lose its gas separation function, and the preparation of polymer-inorganic nanocomposite membranes is complex, making it difficult to achieve stable dispersion of inorganic particles and improve membrane performance.

Method used

Using a composite hollow fiber membrane preparation method, by adding dimethylacetamide, ethyl silicate and polyvinylidene fluoride to the cast film liquid, and after stirring and defoaming, silicon with in-situ formed The hollow fiber membrane of oxide ensures the stable dispersion of inorganic particles, and constrains molecular movement through the interaction between silicon oxide and polymer chain, improving water filtration performance.

Benefits of technology

The stable dispersion and high hydrophilicity of inorganic particles are achieved, the water filtration performance and electrical properties of the membrane are improved, the fluid separation effect is enhanced, and the membrane's compressive and deformation resistance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236698A_ABST
    Figure CN119236698A_ABST
Patent Text Reader

Abstract

The invention discloses a composite hollow fiber membrane and a preparation method thereof, and belongs to the technical field of composite membranes, the method comprises the following steps: a first mixed solution and a second mixed solution are respectively obtained, the first mixed solution comprises dimethylacetamide and ethyl silicate, the second mixed solution comprises dimethylacetamide and polyvinylidene fluoride (PVDF), and the first mixed solution and the second mixed solution are mixed; the first mixed solution or the second mixed solution also contains polyvinyl pyrrolidone (PVP); mixing the first mixed solution and the second mixed solution to obtain a membrane casting solution; and defoaming the membrane casting solution to prepare the composite hollow fiber membrane. Through interaction of in-situ formed silicon oxide and special functional groups of PVP, additional constraint is applied to molecular chain movement of PVP, meanwhile, constraint is applied to molecular movement of PVDF macromolecular chains, and the water filtration performance of the membrane can be changed; the inorganic particles can be stably dispersed in the membrane, have high hydrophilicity, are negatively charged in a normal water environment, and can provide hydrophilic and electrical effects in fluid separation to achieve the effect of improving separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite membranes, and in particular to a composite hollow fiber membrane and a preparation method thereof. Background Art

[0002] The pore size and deformation resistance of ultrafiltration and microfiltration membranes, as well as the hydrophilicity of the membranes are important indicators in the water purification process. At present, the commonly used membrane material polyvinylidene fluoride (PVDF) is a hydrophobic rubber-like polymer material at normal application temperature, so the pore size is sensitive to temperature and pressure, and the water flux decreases with the use time. From the microscopic structure, if the movement of the molecular chain can be constrained, the above indicators can be improved. The intervention of inorganic nanoparticles is a means of restricting the movement of molecular chains, provided that the inorganic particles must be small enough to reach the nanometer level, so that they can provide enough excessive points of action. These nanoparticles must have a sufficiently strong interaction with at least one substance in the membrane; otherwise, the inorganic nanoparticles will self-agglomerate due to their own surface energy, and the performance of the membrane will not only not be improved, but will become worse.

[0003] The loss of gas separation function of the membrane due to the agglomeration of nanoparticles has always been a difficult problem in this field. The preparation of polymer-inorganic nanocomposite water treatment membranes is much more complicated than that of gas membranes because the chemical environment in which such composite water treatment membranes are prepared is more complex.

[0004] At present, silica particles are usually pretreated to enhance the interaction with PVDF, but the result is a composite film in which the inorganic particles cannot be stably dispersed in the polymer. Summary of the invention

[0005] In view of the above technical problems existing in the prior art, the present invention provides a composite hollow fiber membrane and a preparation method thereof, wherein inorganic particles are stably dispersed on the composite hollow fiber membrane to improve the water separation effect.

[0006] The invention discloses a method for preparing a composite hollow fiber membrane, comprising the following steps: respectively obtaining a first mixed liquid and a second mixed liquid, wherein the first mixed liquid contains dimethylacetamide and ethyl silicate, the second mixed liquid contains dimethylacetamide and polyvinylidene fluoride, and the first mixed liquid or the second mixed liquid further contains polyvinyl pyrrolidone; mixing the first mixed liquid and the second mixed liquid to obtain a casting liquid; and degassing the casting liquid to prepare a composite hollow fiber membrane.

[0007] Preferably, the method for preparing the first mixed solution comprises:

[0008] Add dimethylacetamide, ethyl silicate and water under stirring at room temperature, and then add polyethylene glycol after stirring;

[0009] The preparation method of the second mixed solution comprises:

[0010] Add dimethylacetamide and polyvinylidene fluoride at a temperature below 80°C and stir until they are completely dissolved.

[0011] Preferably, ammonia water is also added to the casting solution.

[0012] Preferably, the content of each component in the first mixed solution is:

[0013] 56-60wt% dimethylacetamide, 20-27wt% ethyl silicate, and 10-20wt% polyethylene glycol or polyvinyl pyrrolidone;

[0014] The content of each component in the second mixed solution is:

[0015] 70-75 wt% dimethylacetamide, 20-28 wt% polyvinylidene fluoride, and 5-10 wt% polyvinyl pyrrolidone.

[0016] Preferably, the first mixed solution is prepared by adding 57.1wt% dimethylacetamide, 26.2wt% ethyl silicate, and 2.6wt% purified water under stirring at room temperature, stirring for 30 minutes, then adding 14.1wt% polyethylene glycol, and stirring for 2-3 hours;

[0017] Preparation of the second mixed solution: adding 72.9% dimethylacetamide, 22.0% polyvinylidene fluoride, and 5.1% polyvinyl pyrrolidone under stirring at a temperature of 80°C, and stirring until the polyvinylidene fluoride and polyvinyl pyrrolidone are completely dissolved;

[0018] The first mixed solution and the second mixed solution were mixed at a weight ratio of 0.35:1, and stirring was continued at 50-60° C. for at least 4 hours to obtain a casting solution.

[0019] Preferably, the first mixed solution is prepared by adding 56.6% dimethylacetamide, 26.4% ethyl silicate, 2.7% purified water, and 14.3% polyvinyl pyrrolidone under stirring at room temperature, adding hydrochloric acid to adjust the acidity to pH 2.3, and stirring for 2-3 hours;

[0020] Preparation of the second mixed solution: adding 70.7% dimethylacetamide, 21.3% polyvinylidene fluoride, and 8.0% polyvinyl pyrrolidone under stirring at a temperature of 80°C, and stirring until the polyvinylidene fluoride and polyvinyl pyrrolidone are completely dissolved;

[0021] The first mixed solution and the second mixed solution are mixed at a weight ratio of 0.35:1, and stirred at 50-60° C. for at least 4 hours to obtain a casting solution;

[0022] After degassing, the casting solution is made into a hollow fiber membrane with a reinforced liner on a hollow fiber membrane spinning device.

[0023] Preferably, the first mixed solution preparation method comprises: adding 52.4% dimethylacetamide, 22.0% ethyl silicate, and 3.6% purified water under stirring at room temperature, adding hydrochloric acid to adjust the pH to 2.5, stirring for 1 hour, adding 22.0% polyvinyl pyrrolidone, and stirring for 5-6 hours;

[0024] The second mixed solution preparation method comprises: adding 72.9% dimethylacetamide and 27.1% polyvinylidene fluoride with stirring at a temperature of 85° C., and stirring until the polyvinylidene fluoride is completely dissolved;

[0025] The first mixed liquid and the second mixed liquid were mixed at a liquid weight ratio of 0.4, and after stirring for 20 minutes, 0.43% ammonia water was added, and stirring was continued at 80° C. for at least 4 hours to obtain a casting liquid.

[0026] Preferably, the degassing conditions are: degassing at 30-80° C. for 12-36 hours.

[0027] The present invention also provides a composite hollow fiber membrane prepared by the above preparation method.

[0028] Preferably, the weight percentage of silicon oxide in the composite hollow fiber membrane is 0-4.85%; and the tensile strength at break is 1.4-2.3N.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: additional constraints are imposed on the molecular chain movement of PVP through the interaction between the in-situ formed silicon oxide and the special functional groups of PVP itself, and constraints are imposed on the molecular movement of the PVDF polymer chain, which can change the water filtration performance of the membrane; the inorganic particles can be stably dispersed on the membrane, are highly hydrophilic, and are negatively charged under normal water conditions, which can provide hydrophilic and electrical effects in fluid separation, thereby achieving the effect of improving separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a flow chart of a method for preparing a composite hollow fiber membrane;

[0031] Figure 2 This is the infrared spectrum of product 1 of Example 1

[0032] Figure 3 This is the infrared spectrum of product 3 of Example 3. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0035] like Figure 1 As shown, the preparation method of the composite hollow fiber membrane comprises the following steps:

[0036] Step 101: Obtain a first mixed solution: dimethylacetamide DMAC and tetraethyl orthosilicate TEOS.

[0037] Step 102: Obtain a second mixed solution: dimethylacetamide DMAC and polyvinylidene fluoride PVDF.

[0038] The first mixed solution or the second mixed solution further contains polyvinyl pyrrolidone PvpK30.

[0039] Step 103: Mix the first mixed solution and the second mixed solution to obtain a casting solution.

[0040] Step 104: Degassing the casting solution to prepare a hollow fiber membrane with a reinforced liner.

[0041] Through the interaction between the in-situ formed silicon oxide and the special functional groups of PVP itself, additional constraints are imposed on the molecular chain movement of PVP, and at the same time, constraints are imposed on the molecular movement of the PVDF polymer chain, which can change the water filtration performance of the membrane; the inorganic particles can be stably dispersed on the membrane, are highly hydrophilic, and are negatively charged under normal water conditions. They can provide hydrophilic and electrical effects in fluid separation, achieve the effect of improving separation, and have superior and special separation characteristics.

[0042] The product of the sol chemical reaction is inorganic silicon oxide, including silicon dioxide and silicon hydroxide. The silicon oxide is formed in situ in the organic polymer material forming the hollow fiber membrane through silane oxide. The particle size does not exceed 5 nanometers and is stably and uniformly distributed in three dimensions in the organic membrane.

[0043] In the embodiments of the present invention, polyvinylidene fluoride (PVDF) is provided by Changzhou Guantong New Material Technology Co., Ltd. Polyvinyl pyrrolidone (PvpK30) is provided by Boai Xinkaiyuan Pharmaceutical Co., Ltd. Polyethylene glycol (PEG400) is provided by Zhejiang Sunrise Fine Chemical Co., Ltd. Tetraethyl orthosilicate-28 (TEOS) is provided by Zhangjiagang Jinshilun Chemical Technology Co., Ltd. Concentrated hydrochloric acid, HCl content: 28%. Ammonia water, NH3 content: 25-28%. Dimethylacetamide (DMAC) is provided by Zhejiang Sunrise Fine Chemical Co., Ltd.

[0044] Example 1

[0045] Preparation of the first mixed solution (Solution A): Add 57.1% (weight percentage, the same below) DMAC, 26.2% TEOS, and 2.6% purified water under stirring at room temperature (20-30° C.), stir for 30 minutes, then add 14.1% PEG and stir for 2-3 hours.

[0046] Preparation of the second mixed solution (Solution B): 72.9% DMAC, 22.0% PVDF, and 5.1% Pvp-K30 were added under stirring at 80° C. and stirred until PVDF and Pvp-K30 were completely dissolved.

[0047] Preparation of casting solution: Mix A and B solutions in a weight ratio of 0.35:1 and continue stirring at 50-60°C for 4-6 hours.

[0048] Preparation of composite hollow fiber membrane: After degassing, the casting liquid is made into a hollow fiber membrane with a reinforced lining on a hollow fiber membrane spinning device, which is recorded as product 1.

[0049] Example 2

[0050] Preparation of the first mixed solution (Solution A): Add 56.6% DMAC, 26.4% TEOS, 2.7% purified water, and 14.3% Pvp-K30 under stirring at room temperature (20-30° C.), add concentrated hydrochloric acid to adjust the acidity to pH 2.3, and stir for 2-3 hours.

[0051] Preparation of the second mixed solution (Solution B): 70.7% DMAC, 21.3% PVDF, and 8.0% Pvp-K30 were added under stirring at 80° C., and stirred until PVDF and Pvp-K30 were completely dissolved.

[0052] Preparation of casting solution: Mix A and B solution in a weight ratio of 0.35:1 and continue stirring at 50-60°C for 4-6 hours.

[0053] Preparation of composite hollow fiber membrane: After degassing, the casting liquid is made into a hollow fiber membrane with a reinforced lining on a hollow fiber membrane spinning device, which is recorded as product 2.

[0054] Example 3

[0055] Preparation of the first mixed solution (Solution A): Add 52.4% DMAC, 22.0% TEOS, and 3.6% purified water under stirring at room temperature (20-30°C), add hydrochloric acid to adjust the pH to 2.5, stir for 1 hour, then add 22.0% Pvp-K30 and stir for 5-6 hours.

[0056] Preparation of the second mixed solution (Solution B): 72.9% DMAC and 27.1% PVDF were added under stirring at 85° C. and stirred until PVDF was completely dissolved.

[0057] Preparation of casting solution: Mix A:B solution at a weight ratio of 0.4, stir for 20 minutes, add 0.43% ammonia water (calculated based on the total weight of A and B after mixing), and continue stirring at 80°C for 4-6 hours.

[0058] Preparation of composite hollow fiber membrane: After degassing for 12 hours, the casting solution was made into a hollow fiber membrane with a reinforced liner on a hollow fiber membrane spinning device, which was recorded as Product 3.

[0059] Example 4

[0060] The casting solution was prepared by the method of Example 3. After degassing at 80° C. for 36 hours, the casting solution was made into a hollow fiber membrane with a reinforced liner on a hollow fiber membrane spinning device, which was recorded as Product 4.

[0061] Example 5

[0062] The casting solution was prepared by the method of Example 3, degassed at 80°C for 36 hours, and then the temperature was reduced from 80°C to 60°C to prepare a hollow fiber membrane with a reinforced lining on a hollow fiber membrane spinning equipment, which was recorded as Product 5.

[0063] Example 6

[0064] Preparation of the first mixed solution (Solution A): 52.4% DMAC and 3.6% purified water were added under stirring at room temperature (20-30°C), and hydrochloric acid was added to adjust the pH to 2.5. After stirring for 1 hour, 22.0% Pvp-K30 was added and stirred for 5-6 hours. That is, TEOS was not added to Solution A of Example 3. The rest of the preparation method was the same as that of Example 3, and it was recorded as Product 6. It was used for thermogravimetric analysis and infrared spectrum comparison.

[0065] Thermogravimetric analysis: Table 1 shows the residual values ​​of each product in thermogravimetric analysis at 600°C. Among them, except for the different film-forming temperatures, Examples 4 and 5 are the same as Example 3, and their inorganic content will not be significantly different from that of Example 3. Examples 1 and 2 both have in-situ reactions of TEOS, but no insoluble silicon oxides are detected. This shows that although tetraethyl orthosilicate participates in the early hydrolysis reaction, the later polymerization reaction did not or did not have time to occur before entering the next process. These hydrolysis products may be lost in the form of colloids during the aqueous solution replacement process of the later film formation. The ammonia water added to Examples 3-5 plays a key role in the later polymerization reaction of TEOS to form silicon inorganic oxides. Assuming that all soluble substances have been completely replaced in the solution replacement process of the membrane, the theoretical maximum content of silicon dioxide is 7%, and the actual conversion rate in the example is 69.3%.

[0066] Table 1

[0067] product 6 1 2 3 4 5 content% 0 0 0 4.85 4.85 4.85

[0068] Tensile property analysis: The tensile mechanical properties of the membrane filaments help to explain the filtration properties of the membrane from the microscopic field of molecular motion. The tensile properties must be measured under the condition of removing the membrane lining. In order to avoid the uncertainty of the membrane thickness measurement, the breaking force is used to describe it. The outer diameter of the membrane filament used for the measurement is 1.97 to 1.99 mm, and the initial length of the membrane filament stretching is 5 cm. The results are given in Table 2. The breaking strength and elongation are used to evaluate the mechanical properties of the molecular chain of the membrane filament. The breaking strength is obtained by uniformly stretching the membrane filament until it just breaks through the tensile machine, and the elongation is calculated by the initial length of the membrane filament and the tear length.

[0069] Table 2

[0070] product 1 2 3 Tensile strength at break, N 1.4-1.5 1.6-1.7 2.2-2.3

[0071] The weight percentage of silicon oxide in product 3 is 4.85%. Assuming that the silicon oxide exists entirely in the form of silicon dioxide, its volume percentage is estimated to be less than 3% based on the density of silicon dioxide of 2.65. As can be seen from Table 2, compared with the membrane filaments without silicon oxide, the tensile strength of product 3 is significantly improved. There is a significant interaction between silicon oxide particles and certain organic functional groups in the membrane filaments, which limits the local movement of the molecular chain. One macroscopic manifestation is the increase in tensile strength. It helps the membrane filaments to resist compression and deformation, and thus helps to reduce water flux attenuation during the application process of the membrane, see Table 3. It can also be seen from the stable burst point data in Table 3 that the possibility of local agglomeration of silicon oxide is very small.

[0072] Table 3

[0073]

[0074] The water flux was measured by introducing a certain pressure of gas from the water inlet of the water flux detection device at a pressure of 0.1 MPa, recording the water output of the membrane at 1, 5, 10, 20, 30, and 60 minutes, and converting it into water flux per unit time per unit membrane area LMH (L / (m 2 *h). Bubble point and burst pressure tests are used to evaluate the membrane pore size distribution and the adhesion between the skin layer and the support layer. By slowly increasing the pressure of the test device, record the pressure when the first bubble cluster appears and the pressure when the membrane breaks.

[0075] Infrared spectrum analysis: All membrane fibers are soaked in clean water for a long time and dried to remove soluble substances in the membrane making process. The infrared spectra of product 6 and product 3 are shown in Figure 2 and Figure 3 The only difference in chemical composition between the two is that the membrane of product 3 contains 4.85% silicon oxide. The bending vibration of monomer water occurs at around 1600cm-1, and the bending vibration of hydrogen-bonded water occurs at 1020-1630cm-1; the carbonyl group of DMAC solvent has a clear stretching vibration frequency of 1646cm-1, and the stretching vibration frequency of hydrogen-bonded DMAC carbonyl group occurs at around 1630cm-1. Figure 2 and 3 It can be seen that none of the above four bands appeared, indicating that water and solvent DMAC were basically completely removed during the membrane preparation process. The obvious difference between the two infrared spectra is that the characteristic peak from 1667.23cm-1 ( Figure 2 ) moves down to 1661.87cm-1( Figure 3 ), the characteristic peak of 1667.23cm-1 is caused by the stretching vibration of the free PVP carbonyl group. When silicon oxide exists, the hydroxyl groups on the particle surface provide proton donors and form hydrogen bonds with the proton acceptors of the PVP carbonyl group, causing the stretching vibration frequency of the PVP carbonyl group to shift down to 1661.87cm-1 ( Figure 3 ).

[0076] Figure 3 There is no characteristic peak (1667.23 cm-1) caused by the stretching vibration of the free PVP carbonyl group, so it is reasonable to assume that all the PVP carbonyl groups are hydrogen bonded to the hydroxyl groups on the surface of the silicon oxide particles. Based on this assumption, the size of the silicon oxide particles can be theoretically estimated. The weight ratio of PvpK30 and ethyl tetrasilicate in Example 3 is 1:1. The silicon dioxide SiO formed after the complete hydrolysis of ethyl tetrasilicate is 1:1. 2 or Silicon Hydroxide Si(OH) 4 According to the maximum values, they are 28.85% and 46.15% respectively. From the actual conversion rate of 69.3% in the previous thermogravimetric analysis, it can be obtained that the conversion of PvpK30 and silicon dioxide SiO 2The weight ratio is 5:1, or with silicon hydroxide Si(OH) 4 The weight ratio is 3.1:1. The molecular weight of a single molecule of PvpK30 is 111, and the weight of silicon dioxide SiO 2 and silicon hydroxide Si(OH) 4 The molecular weights of ethyl tetrasilicate and ethyl tetrasilicate are 60 and 96 respectively. From these data, it can be concluded that whether the final reaction product of ethyl tetrasilicate is silicon dioxide SiO 2 Or silicon hydroxide Si(OH) 4 , the ratio of the number of PVP carbonyl groups to silicon oxide particles is 2.7:1. This indicates that a SiO 2 molecule or a Si(OH) 4 The molecules are bonded to nearly three carbonyl groups on the PVP molecular chain. This imposes additional constraints on the movement of the PVP molecular chain, and at the same time constrains the movement of the PVDF molecular chain in the form of mutual entanglement of the molecular chains, thereby improving the tensile strength of the membrane filaments and slowing down the attenuation of water flux from a macroscopic perspective. Since a single silica is only about 0.4 nanometers in spherical shape, it is difficult to observe even with a transmission electron microscope. If the content of silicon oxides generated in situ in the membrane filaments is increased to 30%, these silicon oxides will have the conditions for further polymerization to form large particles, but their size is estimated to be no more than 5 nanometers.

[0077] The above examples only give the membrane properties under some special conditions. By changing the process conditions, the chemical composition of the casting solution and the content of ethyl tetrasilicate, more composite membranes suitable for various industrial applications may be realized. The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite hollow fiber membrane, characterized in that: The following steps are involved: obtaining a first mixed solution and a second mixed solution respectively, wherein the first mixed solution comprises dimethylacetamide and ethyl silicate, the second mixed solution comprises dimethylacetamide and polyvinylidene fluoride, and the first mixed solution or the second mixed solution further comprises polyvinyl pyrrolidone; Mixing the first mixed solution and the second mixed solution to obtain a casting solution; The casting solution is degassed to prepare a composite hollow fiber membrane.

2. The preparation method according to claim 1, characterized in that: The preparation method of the first mixed solution comprises: Add dimethylacetamide, ethyl silicate and water under stirring at room temperature, and then add polyethylene glycol after stirring; The preparation method of the second mixed solution comprises: Add dimethylacetamide and polyvinylidene fluoride at a temperature below 80°C and stir until they are completely dissolved.

3. The preparation method according to claim 1, characterized in that: Ammonia water is also added to the casting solution.

4. The preparation method according to claim 1, characterized in that: The content of each component in the first mixed solution is: 56-60wt% dimethylacetamide, 20-27wt% ethyl silicate, and 10-20wt% polyethylene glycol or polyvinyl pyrrolidone; The content of each component in the second mixed solution is: 70-75 wt% dimethylacetamide, 20-28 wt% polyvinylidene fluoride, and 5-10 wt% polyvinyl pyrrolidone.

5. The preparation method according to claim 1, characterized in that: The specific steps include: Preparation of the first mixed solution: adding 57.1wt% dimethylacetamide, 26.2wt% ethyl silicate, and 2.6wt% purified water under stirring at room temperature, stirring for 30 minutes, then adding 14.1wt% polyethylene glycol, stirring for 2-3 hours; Preparation of the second mixed solution: adding 72.9% dimethylacetamide, 22.0wt% polyvinylidene fluoride, and 5.1wt% polyvinyl pyrrolidone under stirring at a temperature of 80°C, and stirring until the polyvinylidene fluoride and polyvinyl pyrrolidone are completely dissolved; The first mixed solution and the second mixed solution are mixed at a weight ratio of 0.35:1, and stirring is continued at 50-60° C. for 4-6 hours to obtain a casting solution.

6. The preparation method according to claim 1, characterized in that: The specific steps include: Preparation of the first mixed solution: adding 56.6wt% dimethylacetamide, 26.4wt% ethyl silicate, 2.7wt% purified water, and 14.3wt% polyvinyl pyrrolidone under stirring at room temperature, adding hydrochloric acid to adjust the acidity to pH 2.3, and stirring for 2-3 hours; Preparation of the second mixed solution: adding 70.7 wt % of dimethylacetamide, 21.3 wt % of polyvinylidene fluoride, and 8.0 wt % of polyvinyl pyrrolidone under stirring at a temperature of 80° C., and stirring until the polyvinylidene fluoride and polyvinyl pyrrolidone are completely dissolved; The first mixed solution and the second mixed solution are mixed at a weight ratio of 0.35:1, and stirred at 50-60° C. for 4-6 hours to obtain a casting solution; After degassing, the casting solution is made into a hollow fiber membrane with a reinforced liner on a hollow fiber membrane spinning device.

7. The preparation method according to claim 1, characterized in that: The first mixed solution preparation method comprises: adding 52.4wt% dimethylacetamide, 22.0wt% ethyl silicate, and 3.6wt% purified water under stirring at room temperature, adding hydrochloric acid to adjust the pH to 2.5, stirring for 1 hour, adding 22.0wt% polyvinyl pyrrolidone, and stirring for 5-6 hours; The second mixed solution preparation method comprises: adding 72.9 wt % dimethylacetamide and 27.1 wt % polyvinylidene fluoride under stirring at a temperature of 85° C., and stirring until the polyvinylidene fluoride is completely dissolved; The first mixed liquid and the second mixed liquid were mixed at a liquid weight ratio of 0.4, and after stirring for 20 minutes, 0.43 wt % ammonia water was added, and stirring was continued at 80° C. for 4-6 hours to obtain a casting liquid.

8. The preparation method according to claim 1, characterized in that: The degassing conditions are: 30-80℃ for 12-36 hours.

9. A composite hollow fiber membrane prepared by the preparation method according to any one of claims 1 to 8.

10. The composite hollow fiber membrane according to claim 9, characterized in that: The weight percentage of silicon oxide is 0-4.85%; and the tensile breaking strength is 1.4-2.3N.